2014
DOI: 10.1007/s11356-014-3146-7
|View full text |Cite
|
Sign up to set email alerts
|

Climate change and air pollution jointly creating nightmare for tourism industry

Abstract: The objective of the study is to examine the long-run and causal relationship between climate change (i.e., greenhouse gas emissions, hydrofluorocarbons, per fluorocarbons, and sulfur hexafluoride), air pollution (i.e., methane emissions, nitrous oxide emissions, and carbon dioxide emissions), and tourism development indicators (i.e., international tourism receipts, international tourism expenditures, natural resource depletion, and net forest depletion) in the World's largest regions. The aggregate data is us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(79 citation statements)
references
References 25 publications
2
68
0
1
Order By: Relevance
“…Paris, BBC News, 2014). Poor air quality has previously been linked to negative economic impacts as a result of decreased tourism activity (Anaman & Looi, 2000;Sajjad, Noreen & Zaman, 2014), and tourism has also been identified as a significant contributor to air pollution (Sáenz-de-Miera & Rosselló, 2013). This research makes several contributions to the literature and to sustainable tourism management.…”
Section: Discussionmentioning
confidence: 86%
“…Paris, BBC News, 2014). Poor air quality has previously been linked to negative economic impacts as a result of decreased tourism activity (Anaman & Looi, 2000;Sajjad, Noreen & Zaman, 2014), and tourism has also been identified as a significant contributor to air pollution (Sáenz-de-Miera & Rosselló, 2013). This research makes several contributions to the literature and to sustainable tourism management.…”
Section: Discussionmentioning
confidence: 86%
“…Degraded visibility can also significantly reduce tourist demand in Natural Parks, as was the case in the Great Smoky Mountain National Park in the United States (Poudyal, Paudel, & Green, ). In a broader context, Sajjad, Noreen, and Zaman () found that climatic factors and air pollution in some regions of Asia and Africa had a negative impact on tourism indicators during the period 1975‐2012, in the form of deforestation and natural resource depletion.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zeb et al (2014) examined the socioeconomic and environmental factors in SAARC countries and found differential causal connections between energy demand, CO 2 emissions, economic growth, livelihoods and resource depletion. Sajjad et al (2014) indicated climatic threats to international tourism and stress the need to mitigate climatic factors to attract foreign tourists for supporting ecotourism global agenda. Akhmat et al (2014c) in another study confirmed the variability in environmental pollutants due to the conventional usage of energy sources that alter the environment in a form to increase extreme temperature and precipitation rate in SAARC countries.…”
Section: Literature Reviewmentioning
confidence: 99%